Attitudes towards plants - exploring the role of plants' ecosystem services - Dünser, Benno; Möller, Andrea; Fondriest, Valentina; Boeckle, Markus; Lampert, Peter; Pany, Peter (Journal of biological education, 2025)
With biodiversity loss as one of today's most pressing global problems, it is crucial to raise public recognition of this crisis and promote acceptance of conservation efforts. Plants, which typically struggle with low awareness ('plant blindness') and less emotional connection than animals with humans, are facing a special challenge. Promoting positive attitudes towards, and interest in, plants might provide the key to resolve this discrepancy. This study aims to differentiate attitudes and interest within the plant awareness framework while at the same time identify criteria for developing positive attitudes and interest towards plants in students. In a mixed-method approach, a questionnaire with closed and open items on attitudes and interest was developed and administered online to 179 students aged 9-19. Quantitative as well as qualitative results show that 'attitudes towards plants' can be differentiated from 'interest in plants'. Attitudes towards plants were positive, whereas interest in plants was rather low, with cultural and regulating ecosystem services acting as primary reasons for students' positive attitudes. These two components can be easily incorporated in botany teaching in order to promote plant awareness and increase knowledge about their crucial role in ecosystems and global climate, thus raising acceptance for conservation.